How do word valence and classes influence lexical processing? Evidence from virtual reality emotional contexts - Wang, Xiaoying; Zhang, Sumin; Zhang, Xiaohuan (Frontiers in Psychology, 2023)
The current study examines the influence of word class (i.e., noun vs. adjective) and valence (i.e., positive vs. negative vs. neutral) on the processing of emotional words under different virtual reality (VR) emotional contexts. To this end, 115 participants performed a modified affect labeling task after experiencing different VR scenarios. Their galvanic skin responses were also examined to further gauge the different effects of VR contexts. The results demonstrated a rather complicated interaction of word class, valence, and VR context in emotional words processing. Overall, (1) while the processing advantage of positively valenced nouns over adjectives was showed under both positive and negative VR contexts, the processing differences between negatively and neutrally valenced nouns and adjectives were different under different emotional VR contexts; (2) both positive and negative VR contexts could stimulate participants to select more positive words though negatively valenced words were processed more under negative VR context relative to positive VR context; (3) the processing of neutral words were affected by the emotional type of VR contexts, and the processing of neutrally and positively valenced words were similar under positive VR context while that of neutrally and negatively valenced words were similar under negative VR context; (4) the amplitude of galvanic skin responses in positive VR was lower than that in negative VR. The results were interpreted in line with the situation-consistency effects, the mood-consistency effects, the specific nature of VR context, and the different features of different word classes in terms of concreteness, imageability, arousal, and valence.